Problems in northern suburbs - Shedd, Mark R. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1965)
Racial and social problems of the big northern cities will increasingly spread to the suburbs. Educators must be prepared to deal effectively with them. The writer's experiences with the englewood board of education in New Jersey are presented. The school district was reorganized (98 percent negro grammar school was closed and its pupils reassigned to other schools). School organization was changed from a 6-3-3 to a 5-3-4 plan. Prekindergarten, reading special counseling and guidance, curriculum reconstruction, and expanded adult education programs and projects have been introduced and initiated. Future plans and sources of aid and ideas were discussed. This article is published in the "harvard graduate school of education bulletin," volume 9, winter, 1964-65.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Boards of Education; De Facto Segregation; Educational Planning; Racial Integration; School Organization; Social Problems; Suburban Problems; Cambridge -- Massachusetts -- New Jersey -- New Jersey (Englewood)